The Dilemma of Taxation Law for Small Farmer - Ismayantika Dyah Puspasari (Yayasan Rumah Peneleh, 2020)
The purpose of this research is: (1) to find out to what extent the Directorate General of Tax has fully disseminated to all levels of society, especially farmers, regarding the imposition of PP 23 of 2018 for farmers. (2) analyzing tax if farmers are not in the harvest period, which means they do not get income. (3) analyzing the risk of loss to farmers when in a famine. This research uses the descriptive qualitative approach in which the researcher criticized PP 46 of 2013 and PP 23 of 2018 based on the conditions in the field and was supported by various sources. The results of this study indicate that the community is increasingly uneasy with a variety of new regulations that corner, that the income of village farmers is uncertain every month. The application of this taxation regulation needs to be reviewed so that the existing rule does not burden small communities, especially for farmers.